TREM2 triggers microglial density and age‐related neuronal loss. Issue 3 (11th December 2018) - Linnartz‐Gerlach, Bettina; Bodea, Liviu‐Gabriel; Klaus, Christine; Ginolhac, Aurélien; Halder, Rashi; Sinkkonen, Lasse; Walter, Jochen; Colonna, Marco; Neumann, Harald
Abstract: The microglial triggering receptor expressed on myeloid cells 2 (TREM2) signals via the activatory membrane adaptor molecule TYROBP. Genetic variants or mutations of TREM2 or TYROBP have been linked to inflammatory neurodegenerative diseases associated with aging. The typical aging process goes along with microglial changes and mild neuronal loss, but the exact contribution of TREM2 is still unclear. Aged TREM2 knock‐out mice showed decreased age‐related neuronal loss in the substantia nigra and the hippocampus. Transcriptomic analysis of the brains of 24 months old TREM2 knock‐out mice revealed 211 differentially expressed genes mostly downregulated and associated with complement activation and oxidative stress response pathways. Consistently, 24 months old TREM2 knock‐out mice showed lower transcription of microglial ( Aif1 and Tmem119 ), oxidative stress markers ( Inos, Cyba, and Cybb ) and complement components ( C1qa, C1qb, C1qc, C3, C4b, Itgam, and Itgb2 ), decreased microglial numbers and expression of the microglial activation marker Cd68, as well as accumulation of oxidized lipids. Cultured microglia of TREM2 knock‐out mice showed reduced phagocytosis and oxidative burst. Thus, microglial TREM2 contributes to age‐related microglial changes, phagocytic oxidative burst, and loss of neurons with possible detrimental effects during physiological aging. Main Points: TREM2 mutations are linked to neurodegenerative diseases, but its exact role in aging is still unclear. Microglial TREM2 triggers inflammatory reaction, phagocytic oxidative burst and loss of neurons during physiological aging.